Patterns of Substance Abuse in Offenders With Schizophrenia— Illness-Related or Criminal Life-Style? - Stompe, Thomas; Ritter, Kristina; Schanda, Hans (Frontiers in Psychiatry, 2018)
Objective: The impact of substance abuse on violent behaviour in patients suffering from schizophrenia is well known. However, the association between the pattern of substance abuse and certain aspects of criminal behaviour like the severity of offence, the previous history of violence and the age at onset of the criminal career is still unclear. Method: To assess the relationship between substance abuse, schizophrenia and violent behaviour we examined healthy non-offenders; healthy offenders; non-offenders suffering from schizophrenia; and offenders suffering from schizophrenia, with respect to different patterns of substance abuse (none, alcohol only, illicit drugs only, and multiple substances. Results: Healthy offenders as well as offenders and non-offenders suffering from schizophrenia are characterized by increased rates of alcohol and illicit drug abuse. Especially multiple substance abuse appears to lower the threshold of aggression and illegal behaviour. This effect is more pronounced in subjects suffering from schizophrenia. In both offender groups the abuse of psychoactive substances is associated with an earlier onset of the criminal career, but has no impact on the severity of the offences. Conclusion: Our results point to the need for a differentiated view on the contribution of substance abuse to the criminality of subjects suffering from schizophrenia.